The Internationalization of Thai Firms: An Institution-Based View - Thongcharoen, Pakawat (2013)
Internationalization of Thai firms has increased dramatically in the recent years. This research examines outward FDI behavior of Thai firm by using regulative, normative, and cognitive pillars of institution-based view. The research studies he case of Siam City Cement Plc which is a thai firm that has internationalized to three foreign countries, namely, Cambodia, Indonesia, and Bangladesh. This paper presents the findings from institutional perspective. The study identifies that regional integration in South-East Asia, company policy, and social values and industry norms are influential to outward FDI decisions. In addition, the use of other frameworks is suggested to aid the understanding of the behavior.